Competition law and pricing among biologic drugs: the case of VEGF therapy for retinal diseases - Van de Wiele, Victor L.; Hammer, Maximilian; Parikh, Ravi; Feldman, William B; Sarpatwari, Ameet; Kesselheim, Aaron S (Journal of law and the biosciences, 2022)
Neovascular age-related macular degeneration (AMD) is a progressive eye disease and is a leading cause of vision loss in the Western world. Vascular endothelial growth factor inhibitors have become a mainstay of treatment for this disease. Currently, treatment options include three originator biologics with approvals for neovascular AMD (aflibercept, ranibizumab, and brolucizumab-dbll) and one biologic that is commonly used off-label for the condition (bevacizumab). In the USA, Medicare spending on these drugs consistently surpassed